Locus of Control Moderating the Influence of Budgeting Participation on Managerial Performance - Mulyana Machmud; Fyrdha Faradyba Hamzah; Nurfadila Nurfadila; Nurina Saffanah; Alien Akmalia (Atestasi : Jurnal Ilmiah Akuntansi, 2022)
This study intends to investigate the influence of involvement in budgeting on managerial performance and examine if the locus of control variable might operate as a moderating variable to mediate the relationship between budgetary participation and organizational performance. A sample of 56 individuals was collected from eight bank branch offices in Kendari via purposeful sampling, with seven respondents from each branch. The data utilized are primary data gathered through the distribution of questionnaires to all respondents and processed with the assistance of PLS statistical tests. This study reveals that engagement in budgeting has a positive and statistically significant effect on managerial performance. Moreover, the locus of control has a negative but negligibleimpactt on management performance. However, when the locus of control interacts with budgetary participation, it considerably impacts managerial performance. This suggests that the locus of control is suboptimal for tasks other than budgeting, resulting in a decline in the quality of those tasks. An unfavorable work environment can cause it; thus, self-control and the ability of managers or employees to affect the climate are unnecessary. When its activities connect with budgeting activities, it is precise with external effects controlled by a robust internal locus, so different pressures and levels cannot easily affect it. Other moderating variables may impede or enhance budgetary involvement and managerial success. Consequently, future studies might investigate the selection of additional moderating variables.